Mutational Analysis of Pre-miR-184 and hsa-mir-568 in Greek Patients With Sporadic Keratoconus. Issue 5 (May 2016) - Moschos, Marilita M.; Droutsas, Konstantinos; Sioziou, Anna; Dettoraki, Maria; Gazouli, Maria
Abstract : Purpose: Despite numerous studies, the causes of keratoconus (KC) remain indefinable. Recently, polymorphisms in the seed region of miR-184 have been identified in familial severe KC and stromal thinning (endothelial dystrophy, iris hypoplasia, congenital cataract, and stromal thinning [EDICT]) syndrome. In this study, we conducted genotyping of microRNA genes localized in the reported KC loci, in a well-defined cohort of Greek sporadic KC patients. Methods: A case–control panel with 61 KC patients and 120 healthy controls was surveyed. DNA from each individual was genotyped for the rs41280052, located within the pre-miR-184 sequence, and hsa-mir-568 rs149509568 polymorphisms, by allele-specific polymerase chain reaction and direct sequencing. Results: Regarding rs41280052, no significant association with KC was observed. The T allele of the rs41280052 was present in 5.74% of KC patients and in 8.75% of healthy controls [ P = 1.00, odds ratio (OR): 1.82, 95% confidence interval: 0.11–29.66]. However, the minus allele (G) of the rs149509568 polymorphism was found to be overrepresented in KC patients ( P = 0.04, odds ratio: 5.08, 95% confidence interval: 0.97–26.61). Conclusions: Our results demonstrated a significant association between sporadic KC and hsa-mir-568 rs149509568 polymorphism, suggesting a potential role of the has-mir-568 in KC pathogenesis.